(untitled) (Research, Society and Development, 2020)
Palliative care refers to the treatment to improve the conditions for the physical and psychological well-being of the patients and also of their relatives during the confrontation of terminal illnesses, from the early recognition, religious analysis and pain relief based on the aspects of physical, spiritual and psychosocial order. The objective of the study was to know the care performed by nurses with terminal patients in a hospital of high complexity in Teresina-PI. This is a qualitative, descriptive study. The research was performed in all hospitalization units that had terminal patients. Eleven nurses who provided direct assistance to terminal patients participated in the study. It was used with questions directed to the characterization of the interviewees and guided to the guiding questions. The analysis of the data was performed using the technique of content analysis proposed by Bardin. The accomplishment of measures of comfort, pain relief, psychological support and therapeutic communication with establishment of bond between professionals, family and patient, are extremely important factors for individuals facing a terminal illness. The work of the Nursing team in palliative care contributes to the maintenance of quality of life of terminal patients and from this, there is a growing need for qualified and specialized professionals to work in the care of this clientele in hospital institutions of Cheers.